HOW DO TEACHERS APPROACH INNOVATIONS: UPPER BASIC SCHOOL TEACHER’S ATTITUDE TOWARDS SCHOOLS CONNET AND MULTI-CHOICE RESOURCE CENTRES IN ILORIN, NIGERIA - Yusuf, A.; Ajidagba, U. A.; Yusuf, H. T.; Amali, I. O. O.; Bello, M.; Oniye, M. I. (European Scientific Journal, ESJ, 2012)
The purpose of the study was to find the attitude of upper basic school teachers towards Schools ConNet/ Multi- choice Resource Centres put in place in upper basic schools in Ilorin. A questionnaire was administered to 288 upper basic school teachers in 28 public upper basic schoolsand the data obtained were analysed using frequency count and percentage. The study revealed that the upper basic school teachers showed positive attitude to Schools ConNet/ Multi- choice Resource Centres, while the use ofthe Schools ConNet/ Multi- choice Resource Centres amongteachers in basic schools was found to be low. The positive attitudes of teachers towards Schools ConNet/ Multi- choice Resource Centres is asignificant factor which will contribute to integration of Information Technology the teacher education curriculum in Nigeria. It is therefore recommended that IT should be integrated into teacher education curriculum especially in the area of pedagogy to develop the required skills of using IT in teaching.